Epidemiology Characteristics of Constipation for General Population, Pediatric Population, and Elderly Population in China - Huikuan Chu; Likun Zhong; Hai Li; Xiujing Zhang; Jingzhi Zhang; Xiaohua Hou (Gastroenterology Research and Practice)
Objective. To acquire more data about the epidemiologic characteristics of constipation in different kinds of populations in China. Methods. Using “constipation” and “China” as search terms; relevant papers were searched from January 1995 to April 2014. Data on prevalence, gender, diagnostic criteria, geographical area, educational class, age, race, and physician visit results were extracted and analyzed. Results. 36 trials were included. Prevalence rates of constipation in elderly population (18.1%) and pediatric population (18.8%) were significantly higher than that in general population (8.2%). Prevalence of constipation defined by non-Rome criteria was higher than that by Rome criteria in general population. Prevalence rates of constipation were different for different geographical area. People with less education were predisposed to constipation. In pediatric population, prevalence of constipation was the lowest in children aged 2–6 years. Prevalence of constipation in ethnic minorities was higher than that in Han people. People with constipation were predisposed to FD, haemorrhoid, and GERD. Only 22.2% patients seek medical advice in general population. Conclusions. In China, prevalence of constipation was lower compared with most of other countries. The factors including female gender, diagnostic criteria, geographical area, age, educational class, and race seemed to have major effects on prevalence of constipation.